Gas-phase Oxidation of Piperidine by "Green Oxidants" H2O2 and N2O - Nagiev, Tofik; Ali-zadeh, Nahmad; Nagieva, Inara (European Journal of Applied Sciences, 2022)
Reactions of piperidine oxidation by hydrogen peroxide and nitrogen oxide (1) were investigated experimentally in the gas phase and at atmospheric pressure without the use of catalysts. The reaction site for selective oxidation of piperidine by hydrogen peroxide and nitric oxide (1) was identified, and consequently, optimal conditions for obtaining pyridine and 2,3,4,5-tetrahydropyridine from piperidine were revealed. Effect of the process parameters on reaction determinants in coherently synchronized reactions of piperidine dehydrogenation and decomposition of hydrogen peroxide and nitric oxide was demonstrated (1).